The prevalence of frailty among older adults with maintenance hemodialysis: a systematic - Juanjuan Li; Wenyi Xiao; Lijuan Wang; Miao Zhang; Yurong Ge (BMC Nephrology)
Abstract Background To evaluate the epidemiological data on the prevalence of frailty and prefrailty in individuals aged 60 years or older on MHD patients. Methods PubMed, Web of Science, Embase, CNKI, WanFang, CBM, and VIP were searched from inception to February 2023 using combinations of subject words and free words. The methodological quality of all the selected studies was assessed using the Joanna Briggs Institute Critical Appraisal of Epidemiological Studies Checklist and Newcastle‒Ottawa Cohort Quality Assessment Scale. Random effects meta-analysis was used to pool estimates from different studies. Subgroup analysis and meta-regression were performed to explore potential sources of heterogeneity. Results Of the 4,190 documents retrieved, 16 observational studies involving 2,446 participants from 8 countries were included in this systematic review. Among older adults receiving MHD, the overall prevalence of frailty and prefrailty was 41% (95% CI = 34–49%) and 37% (95% CI = 26–48%), respectively, with considerable heterogeneity. The pooled prevalence of frailty was greater among individuals aged > 70 years (45%) than among those aged ≤ 70 years (37%). However, subgroup analyses indicated that the confidence intervals for the age group overlap substantially. Conclusion Our research showed that the prevalence of frailty and prefrailty in older patients with MHD are high. Trial registration The PROSPERO registration number for this study was CRD42023442569.